Luminescence of CWO single crystals containing various defects - Grinyov, B.V.; Moroz, Z.T.; Nagornaya, L.L.; Pashkovsky, M.S.; Ryzhikov, V.D.; Tupitsyna, I.A.; Apanasenko, A.L. (Functional Materials, 2005)
Influence of dopant-induced defects on luminescence and performance characteristics of CWO crystals has been studied. Мо and Fe have been shown to give rise to a specific "red" emission component with decay time of several hundreds of microseconds or more, while trivalent dopants cause formation of deep charge carrier traps responsible for the millisecond range afterglow. These defects give rise also to the color centers causing absorption in the intrinsic emission band, thus deteriorating the crystal scintillation parameters. The studies performed allowed to develop a technology of large high-quality CWO crystals. The tomographic elements manufactured from those crystals showed an afterglow of less than 100 ppm after 20 ms and the light yield of about 20,000 photons per MeV.